Learning to Navigate a New Financial Technology - BREZA, EMILY; KANZ, MARTIN; KLAPPER, LEORA (Journal of Finance, 2026)
ABSTRACT We present results from a field experiment that introduced digital payroll accounts to unbanked factory workers to examine how inexperienced consumers learn to use a new financial technology. We find that exposure to payroll accounts leads to increased account use, accelerated learning, and avoidance of common consumer protection risks. Those receiving electronic wage payments gradually build trust in the technology, learn to use accounts without assistance, and avoid illicit fees. Using experimental variation in assignment to bank versus mobile money accounts, we show that these impacts are concentrated in mobile money accounts, the newer, more complex, and less trusted financial technology.